GAMBARAN KEJADIAN GANGGUAN FUNGSI PARU PADA PEKERJA PENGASAPAN IKAN di BANDARHARJO SEMARANG - Rachmawati, Annisa; Darundiati, Yusniar Hanani; Dewanti, Nikie Astorina Yunita (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
The smoking fish center in Bandarharjo is the largest center in Semarang city and it still uses traditional smoking method. The fuel used is coconut shell, coconut husk and corncob which is one of activity of burning biomass. Biomass burning has the risk of respiratory infections and obstructive pulmonary disease. The factors that can affect the impaired lung function are age, sex, work period, long exposure, nutritional status, smoking habits, exercise habits, and history of respiratory diseases. The aim of this study is to determine the description of the incidence of impaired lung function in smoking fish workers. This research is descriptive research with cross sectional study. The unit of analysis in this study is the workers in the smoking fish. Determination of sample is using purposive sampling method, so that got sampel as many as 36 respondents. In this study, most of the workers were ≥30 years old (96.7%), female (93.3%), medium-term (30%), long service period (70%), long exposure ≥ 8 hours per day (93.3%). Most of them have more nutritional status (73.3%) All workers do not use masks (100%), have no smoking habit (93,3%) and no sport habit (93,3). Most of the workers had impaired lung function, with restriction disorder (26.7%), moderate restriction disturbance (26.7%), mild restriction disorder (16.7%), severe restriction disorder (6.7%) and mixed disorder (16.7%).The conclusion of this research is that most of the working of fish curing have impaired lung function.